ISTIRAHATLAH KATA-KATA: SEBUAH KAJIAN RESEPSI SASTRA - Yeni Yulianti (Balai Bahasa Kalimantan Barat, 2017)
In order to bring the nation's children are now in a global context, many ways taken. Specifically for specialization Indonesian language and literature, one way through the movie. One relatively effective media to introduce poetry simultaneously promote literacy movements. This widescreen will extend embraced within reach far more layers of society. Call it a movie called Rest Words (2017); The film won many awards are made based on the poems of a poet who is an activist, Wiji Thukul. Through movies, poems become scattered and can be enjoyed by many people, is no longer exclusively into their own or some people as long as we observe. Stretching present diverse literary reception after the premiere of Rest Words. The actual reader Iser a term to describe people give interpretations, which to him that the work of the